Keterwakilan Perempuan dalam Politik: Analisis Rendahnya Anggota Legislatif Terpilih Perempuan di DPRD Kabupaten Sabu Raijua Pada Pemilu 2024 - Lodia Lede Hiku; Yeftha Y. Sabaat; Stefanus Triadmaja; Rex Tiran (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2025)
This research is entitled “Women’s Representation in Political (Analysis of the Low Number of Elected Female Legislative Members in the Sabu Raijua Regency DPRD in the 2024 Election).” The low representation of women in politics is a significant issue in various regions, including Sabu Raijua Regency. This study aims to analyse the low representation of women in politics and the factors that hinder women from becoming legislative members in the Sabu Raijua Regency DPRD in the 2024 elections using Gender Theory, which focuses on three derivatives of the theory, namely gender issues, gender ideas, and gender representation. The results of the study show that the obstacles faced by women are not only related to individual capabilities, but are also the result of social constructs influenced by gender issues, gender ideas, and gender representation. Women are often faced with domestic burdens, financial constraints, and a lack of training from political parties, which limits their political capacity. Patriarchal customs also reinforce the notion that men are more suitable for leadership, while women are seen as quota fillers. As a result, representation is more symbolic than substantial, as evidenced by the fact that only two women have won seats in the Regional People's Representative Council (DPRD), one of whom was through the PAW mechanism. Barriers include traditional norms, gender stereotypes, and social legitimacy; lack of support and strategy from political parties; and financial constraints and campaign capital.